Pola Pemetaan Distribusi Air Lindi Pada Kualitas Air Permukaan Di Kawasan TPA Kandis Kabupaten OKU - Lucyana Lucyana; Eka Rizki Meiwinda; Tommy Romansyah (UNIVED Press, 2023)
The quality and quantity of groundwater can decrease, one of the causes is the waste management carried out at the Final Waste Management Site (TPA). . The values of Fe, Cd, Cr, NO2, and Zn at station 1 were above the BML values, while the values of Fe, Cd, Zn and Pb at station 2 while the values of Cd, Zn and Pb at station 3 were above the recommended BML values. The waste in the Simpang Kandis TPA has not been properly managed, causing leachate to spread to the environment around the Simpang Kandis TPA.